EXPERIMENTAL TEST OF FRAMING AND NON-PROFESSIONAL INVESTOR’S DECISION: STUDY OF RISK INFORMATION IN IFRS NO. 7 - Negina Kencono Putri; Zaki Baridwan; Supriyadi Supriyadi; Ertambang Nahartyo (Universitas Hayam Wuruk Perbanas, 2012)
This study attempts to predict the impact of framing in decisions that preceded the presence ofrisk information in the format of value at risk and sensitivity analysis, and also preliminary evidencein assessing the implementation of a predetermined standard. It was done experimentallywith the design of between-within-subject design and 2 (Format: VAR & SA) x 2 (Frame: Gain &Loss) factorial using 15 students of Master of Accounting program and PPAK program that actsas a participant in the experiment. The result showed that there are no differences in decisionsmade by participants if the information is presented in the form of value at risk or sensitivityanalysis. This suggests that participants did not give different weights to the format of risk reportsthat are presented, so it can be concluded that both the format of risk reports in this studydid not affect the investment decisions. Thus, companies can choose one of two formats to meetthe obligations of the risk statement presentation required by the IFRS No. 7. This study alsoprovides additional evidence that the individual decisions can be influenced by framing andproves that theory within the framework of Prospect Theory plays a role in investment decisions.